Analisis Pemberatan Pidana Dan Konstruksi Concursus Terhadap Anggota Polri Dalam Tindak Pidana Kepemilikan Dan Peredaran Narkotika - Indiartha Billah Azizah (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
Police involvement in narcotics cases represents a legal irony that erodes public trust in law enforcement institutions. Police officers ought to serve as role models, yet they instead engage in the very crimes they are sworn to prevent. This study examines whether police officers involved in narcotics cases can face harsher penalties. We also seek to understand how the legal system addresses cases involving officers who accept bribes and participate in narcotics-related offenses. Our research employs a normative legal method, utilizing both statutory and conceptual approaches. The findings indicate that police officers involved in narcotics cases may be subject to more severe punishment due to their abuse of authority and betrayal of the public trust. When a police officer commits a narcotics offense and accepts a bribe, the situation constitutes concursus realis—meaning multiple distinct criminal acts involving different protected legal interests have occurred. Officers involved in such cases must be punished in accordance with applicable law. The public has a right to justice; therefore, judges must take into account the official status of the police officer when handing down a sentence. It is hoped that doing so will help restore public confidence in law enforcement institutions.